2012
DOI: 10.1007/s10096-012-1697-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of Staphylococcus aureus bacteremia in patients with liver cirrhosis

Abstract: Patients with liver cirrhosis (LC) have impaired immunity and thus are predisposed to infections. Few studies have attempted to evaluate Staphylococcus aureus bacteremia (SAB) in LC patients. Therefore, this study prospectively evaluated the clinical characteristics and outcomes of 642 episodes of SAB from August 1, 2008 to September 31, 2010. Of 642 patients with SAB, 109 (17.0 %) were classified as LC patients whereas the remaining 533 (83.0 %) were classified as non-LC patients. The 30-day mortality rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Indices of the severity of comorbidities and illness are known to be associated with death of patients with S. aureus bacteremia (SAB) [11-13,30,31], and most previous studies investigated the factors associated with late mortality, such as 30-day mortality [11-13,30,31]. The exception is a recent study by Gasch et al [6], which looked at early mortality, defined as death within 2 days of the onset of MRSAB, as in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Indices of the severity of comorbidities and illness are known to be associated with death of patients with S. aureus bacteremia (SAB) [11-13,30,31], and most previous studies investigated the factors associated with late mortality, such as 30-day mortality [11-13,30,31]. The exception is a recent study by Gasch et al [6], which looked at early mortality, defined as death within 2 days of the onset of MRSAB, as in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ST131-producing CTX-M-15 has been found prevalent in Japan, with rare cases described in Indonesia and China. [10-13] Until this report, a detailed report of virulence data related to ST131 in Taiwan was lacking. In our previous study, we found ST131 in about one third of patients with bacteremia and ESBL-EC.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study examined S. aureus bacteraemia in patients with and without cirrhosis. 16 Patients with cirrhosis had a higher 30 day mortality than those without cirrhosis: septic shock and advanced liver disease (Child–Pugh class 3) were associated with increased mortality. Finally, Gustot et al .…”
Section: Discussionmentioning
confidence: 98%
“…These findings add to the limited information available on MRSA carriage and infection in patients with cirrhosis. 1116 …”
Section: Introductionmentioning
confidence: 99%